Naming Themes in Interpretative Phenomenological Analysis (IPA): Recommendations and Examples - Dennis Nigbur; Sheryl L. Chatfield (International Journal of Qualitative Methods)
In qualitative research, theme typically refers to an identified trend running through the data. Themes play a prominent role in interpretative phenomenological analysis (IPA) and may serve as a framework for presentation. Although comprehensive resources are available to guide researchers through stages of IPA analysis, there is far less information on specific strategies for associating a theme with a name or label for IPA, or for other qualitative approaches. Therefore, the purpose of this paper is to present strategies for thoughtful development of IPA theme names. To this end, we present and summarize available theme-naming guidance associated with multiple methods including IPA and thematic analysis. We supplement this with examples from prior IPA research studies we believe illustrate effective theme names, organized in three broad categories of theme focus, phrasing, and structure. Within these categories we provide guidelines for researchers to consider to best address the research purpose and most effectively communicate the key findings.